2020
DOI: 10.3390/biom10101397
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Action of Hydroxytyrosol in Wound Healing: An In Vitro Evidence-Based Review

Abstract: Hydroxytyrosol (HT) is an essential molecule isolated from the phenolic fraction of olive (Olea europaea). HT has been implicated for its health-stimulating effect mainly due to its antioxidative capacity. The current review summarises and discusses the available evidence, related to HT activities in wound healing enhancement. The literature search of related articles published within the year 2010 to 2020 was conducted using Medline via Ebscohost, Scopus, and Google Scholar databases. Studies were limited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…We assessed HT activity in wound healing phases that are not well-defined. The wound is a pathological condition with the destruction of the physiological microstructure and a loss of tissue function by a chemical, thermal, or physical injury [ 49 , 50 ]. The wound healing process is mediated by the activation of local and systemic cells that cooperate to restore skin integrity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We assessed HT activity in wound healing phases that are not well-defined. The wound is a pathological condition with the destruction of the physiological microstructure and a loss of tissue function by a chemical, thermal, or physical injury [ 49 , 50 ]. The wound healing process is mediated by the activation of local and systemic cells that cooperate to restore skin integrity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, excessive levels of inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) or interleukin 6 (IL-6), IL-8, and IL-1β are implicated in a wound healing delay [ 54 ]. In this first phase, HT acts as a powerful anti-inflammatory molecule that relieves the inflammatory state favoring the wound healing progression [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HT is an essential molecule isolated from Olea europea , known for its antioxidative capacity. This review highlights the positive influence towards wound healing by the actions mediated by HT, becoming a bioactive compound highly recommended for wound care applications [ 7 ]. Kim et al demonstrated that soybean embryo extract (SEE), which is a bioactive phytoestrogen, exerts anti-obesity effects through the activation of adipose tissue metabolism and exhibits a synergistic effect upon co-treatment with enzymatically modified isoquercitrin (EMIQ) [ 8 ].The study of Piatczak et al examined the phenolic compounds in hydromethanolic extracts of Salix alba (L.) leaves and bark, as well as their antioxidant activity and cytotoxic potential.…”
mentioning
confidence: 99%